2022
DOI: 10.4081/ejh.2022.3275
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-17-3p is upregulated in psoriasis and regulates keratinocyte hyperproliferation and pro-inflammatory cytokine secretion by targeting <em>CTR9</em>

Abstract: Psoriasis is a chronic inflammatory skin disease. Although miRNAs are reported to be associated with the pathogenesis of psoriasis, the contribution of individual microRNAs toward psoriasis remains unclear. The miR-17-92 cluster regulates cell growth and immune functions that are associated with psoriasis. miR-17-3p is a member of miR-17-92 cluster; however, its role in dermatological diseases remains unclear. Our study aims at investigating the effects of miR-17-3p and its potential target gene on keratinocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Regarding miR‐17‐5p, our results showed a differential expression of this miRNA in treated patients, with pronounced up‐regulation within chronic patients compared to those developing a mild form. Previously, an up‐regulation of the other arm of miR‐17, miR‐17‐3p, in psoriatic lesions compared to normal skin specimens has been reported 56 . This cutaneous increase in miR‐17 attenuates the SOCS1 gene, leading to an accentuated production of CXCL9 and CXCL10 chemokines and subsequently promoting T‐cell infiltration of the skin 24 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding miR‐17‐5p, our results showed a differential expression of this miRNA in treated patients, with pronounced up‐regulation within chronic patients compared to those developing a mild form. Previously, an up‐regulation of the other arm of miR‐17, miR‐17‐3p, in psoriatic lesions compared to normal skin specimens has been reported 56 . This cutaneous increase in miR‐17 attenuates the SOCS1 gene, leading to an accentuated production of CXCL9 and CXCL10 chemokines and subsequently promoting T‐cell infiltration of the skin 24 .…”
Section: Discussionmentioning
confidence: 91%
“…Previously, an up-regulation of the other arm of miR-17, miR-17-3p, in psoriatic lesions compared to normal skin specimens has been reported. 56 This cutaneous increase in miR-17 attenuates the SOCS1 gene, leading to an accentuated production of CXCL9 and CXCL10 chemokines and subsequently promoting T-cell infiltration of the skin. 24 In the same context, a recent study identified miR-17 as a key element in the emergence of pathogenic CD4 + T-cells and autoantibody deposition, resulting in skin lesions, an important feature of cutaneous chronic graft-versus-host disease.…”
Section: Panther Pathway Accessionmentioning
confidence: 99%
“…Ulcerative colitis [34] miR-29 Depletion of the miR-29a/b1 cluster impacts the fibroinflammatory mechanisms AP [35] miR-34 miR-34-LGR4 changed the activity of the NF-κB signaling pathway Chronic wound inflammation [36] Downregulates SIRT1 NEC [37] miR-Increased activity of the STAT3 and ERK pathways, thereby promoting keratinocyte growth [38] miR-206-3p Repressed vascular-specific CXCR4 Atherosclerosis [39] miR-7 Inhibits PTEN and increases the activation of the PI3K/Akt signaling pathway SLE [40] miR-17-3p Activates the downstream STAT3 signaling pathway by targeting CTR9 Psoriasis [41] Anti-inflammatory miRNAs miR-10…”
Section: Main Functions Disease Referencesmentioning
confidence: 99%